2015
DOI: 10.1371/journal.pone.0133547
|View full text |Cite
|
Sign up to set email alerts
|

Practical Support from Fathers and Grandmothers Is Associated with Lower Levels of Breastfeeding in the UK Millennium Cohort Study

Abstract: Mothers face trade-offs between infant care and subsistence/economic activities. In traditional populations, allomothers such as fathers and grandmothers support mothers with young infants, allowing them to reduce labour activities and focus on breastfeeding. Similarly, the positive impact of social support on breastfeeding has been highlighted in developed populations. However, these studies have generally focused on emotional support from fathers, peers and healthcare professionals. Given the availability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
98
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 38 publications
9
98
0
6
Order By: Relevance
“…Alloparenting can also differentially affect the fitness of mothers among and within populations of the same species because the rates and types of interactions are not always consistent across individuals (e.g. meerkats, S. suricatta  [26]; sperm whales, Physeter macrocephalus  [4]; black-and-white ruffed lemurs, Varecia variegata  [27]; humans, H. sapiens  [28]). In some cases, alloparenting may seemingly have no direct fitness benefits to mothers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Alloparenting can also differentially affect the fitness of mothers among and within populations of the same species because the rates and types of interactions are not always consistent across individuals (e.g. meerkats, S. suricatta  [26]; sperm whales, Physeter macrocephalus  [4]; black-and-white ruffed lemurs, Varecia variegata  [27]; humans, H. sapiens  [28]). In some cases, alloparenting may seemingly have no direct fitness benefits to mothers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review showing the positive impact of grandmother attitudinal support for breastfeeding on breastfeeding outcomes supports this claim [Negin, Coffman, Vizintin, & Raynes-Greenow, 2016]. However, new research in Britain suggests that there are multiple pathways by which support may influence breastfeeding -emotional support may increase its likelihood, while practical support like child care may reduce the likelihood of breastfeeding [Emmott & Mace, 2015]. Ethnographic studies with African American mothers in the southern USA have shown that negative grandmother attitudes toward breastfeeding and increased physical proximity to mother-baby dyads are a barrier to exclusive breastfeeding [Bentley, Gavin, Black, & Teti, 1999].…”
Section: Intersibling and Intergeneration Effectsmentioning
confidence: 99%
“…Modifiable factors include psychosocial constructs from health behavior theories (attitude, intention, and self-efficacy), 2225 parental feeding styles (responsive feeding), 2633 and interpretation of infant fussiness. 3439 Specific to breastfeeding, substantial evidence shows that more positive attitudes, greater levels of social support, and greater breastfeeding self-efficacy are each associated with higher rates of breastfeeding initiation and/or longer durations of exclusive or partial breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…3439 Specific to breastfeeding, substantial evidence shows that more positive attitudes, greater levels of social support, and greater breastfeeding self-efficacy are each associated with higher rates of breastfeeding initiation and/or longer durations of exclusive or partial breastfeeding. 2225 …”
Section: Introductionmentioning
confidence: 99%